Archive.org sebagai Perpustakaan Digital Penyedia Koleksi Langka bagi Sejarawan dalam Era Revolusi Industri 4.0 - Arifin, Faizal (Historia Madania: Jurnal Ilmu Sejarah, 2022)
This study discusses the history and functions of the archive reference service on the archive.org site, which is important for historians. Archive.org is a collection managed by a non-profit organization involving many institutions and educational institutions. Archive.org has various rare collections, such as books or manuscripts published from the 8th to 21st centuries. These rare collections can be a primary source for researchers who use archives, especially historians. Therefore, this study can be used as an initial reference to introduce archive.org not only to historians but also to journalists, writers, and librarians. The research method used is a qualitative approach with a literature study method. The results show that archive.org provides reference services, especially for rare reference collections. The service process is conducted not through physical contact but virtually and digitally. Based on the results, it was found that in addition to providing archives that can be accessed in full without asking for services, archive.org also provides digital book lending services such as libraries. Archive.org can be a reference for implementing digital libraries that provide full access for the public to collaborate in the era of the Industrial Revolution 4.0.